2020
DOI: 10.1038/s41598-020-61738-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of female and male gonads in juvenile snakeskin gourami (Trichopodus pectoralis)

Abstract: na-nakorn 2* the snakeskin gourami (Trichopodus pectoralis) exhibits sexual dimorphism, particularly in body size. Since the snakeskin gourami is usually marketed during sexual maturation, the sexual size dimorphism has become an economically important trait. Sex-biased gene expression plays a key role in phenotypic sexual dimorphism. therefore, using high-throughput RnA sequencing (RnA-seq) technology, we aimed to explore the differentially expressed genes (DEGs) in ovary and testis during sex differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 65 publications
1
8
1
Order By: Relevance
“…All of the DEGs discovered in this inquiry were annotated using a variety of functional databases. We found that 11.12% of the assembled unigenes had a substantial annotation to all databases (NR, Swiss-Prot, Pfam, COG, GO, and KEGG), which was significantly higher than previous studies of juvenile snakeskin gourami female and male gonads, which showed 9.8% of assembled matching (Boonanuntanasarn et al, 2020). When the DEGs were enriched in the KEGG database, certain pathways relevant to the development of fish ovary were discovered including the Wnt signaling pathway and the GnRH signaling pathway, and this was consistent with a previous study by H. Liu et al (2019).…”
Section: Transcriptome Assembly and Annotation Analysiscontrasting
confidence: 72%
See 1 more Smart Citation
“…All of the DEGs discovered in this inquiry were annotated using a variety of functional databases. We found that 11.12% of the assembled unigenes had a substantial annotation to all databases (NR, Swiss-Prot, Pfam, COG, GO, and KEGG), which was significantly higher than previous studies of juvenile snakeskin gourami female and male gonads, which showed 9.8% of assembled matching (Boonanuntanasarn et al, 2020). When the DEGs were enriched in the KEGG database, certain pathways relevant to the development of fish ovary were discovered including the Wnt signaling pathway and the GnRH signaling pathway, and this was consistent with a previous study by H. Liu et al (2019).…”
Section: Transcriptome Assembly and Annotation Analysiscontrasting
confidence: 72%
“…Sex differentiation is considered to be the most significant factor in the evolution of species (Boonanuntanasarn et al, 2020; Taboada et al, 2014). A fascinating scientific problem, sex determination and differentiation may influence biological reproduction and cause sexual morphism.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the gonad of the olive flounder, Paralichthys olivaceus, PIWI-related gene expression was 2,000 fold higher in the testis compared to the ovary (Zhang et al, 2016). Similar differences in PIWI-related genes were corroborated in the gonads of turbot (Scophthalmus Maximus), snakeskin gourami (Trichopodus pectoralis), and yellowfin seabream (Acanthopagrus latus) (Wang et al, 2018;Boonanuntanasarn et al, 2020;Li et al, 2020).…”
Section: Sex Differences In Transposable Elementsmentioning
confidence: 77%
“…Examples of this are the Spats1 homolog from bony fish Oryzias latipes (GenBank Access number FS557457), cartilaginous fish Callorhinchus mili (access number XP_007901502.1), cephalochordates Branchiostoma belcheri and Branchiostoma floridae (access numbers XP_019647808 and XP_002590276.1, respectively), hemichordate Saccoglossus kowalevskii (access number XP_002731024.1), echinoderm Strongylocentrotus purpuratus (access number XP_001184069.1), brachiopod Lingula anatina (access number XP_013389114.1), and the mollusk Octopus bimaculoides (access number XP_014774497.1), among others. Of note, a recent study in juvenile snakeskin gourami fish also identified Spats1 among the top differentially expressed genes in testis, as compared to ovary [ 35 ].…”
Section: Resultsmentioning
confidence: 99%